Triple‐Helix‐Stabilizing Effects in Collagen Model Peptides Containing PPII‐Helix‐Preorganized Diproline Modules. Issue 14 (3rd February 2020) - Maaßen, Andreas; Gebauer, Jan M.; Theres Abraham, Elena; Grimm, Isabelle; Neudörfl, Jörg‐Martin; Kühne, Ronald; Neundorf, Ines; Baumann, Ulrich; Schmalz, Hans‐Günther
Abstract: Collagen model peptides (CMPs) serve as tools for understanding stability and function of the collagen triple helix and have a potential for biomedical applications. In the past, interstrand cross‐linking or conformational preconditioning of proline units through stereoelectronic effects have been utilized in the design of stabilized CMPs. To further study the effects determining collagen triple helix stability we investigated a series of CMPs containing synthetic diproline‐mimicking modules (ProMs), which were preorganized in a PPII‐helix‐type conformation by a functionalizable intrastrand C2 bridge. Results of CD‐based denaturation studies were correlated with calculated (DFT) conformational preferences of the ProM units, revealing that the relative helix stability is mainly governed by an interplay of main‐chain preorganization, ring‐flip preference, adaptability, and steric effects. Triple helix integrity was proven by crystal structure analysis and binding to HSP47. Abstract : Collagen model peptides represent attractive materials for biomedical applications. To rationally design peptide properties, knowledge about the impact of structural modifications is fundamental. Therefore, the impact of covalent diproline rigidification was studied and correlated with theoretical findings to understand the symphony of (de)stabilizing effects in the triple helix.